Negotiating Digital Spaces in Everyday Life: A Case Study of Indian Women and Their Digital Use - Paul, Anindita, and Kim M. Thompson (First Monday, 2018)
New developments in digital technology and better and affordable access allow women unprecedented access to information and communication networks — if they are able to use digital technologies to access networks and digital information. This study presents a case study of motivations of women to use information and communication technologies (ICT) in a ubiquitous information environment. This study follows an interpretive paradigm to explore an understanding of culture and gender in a middle-class Indian context. Women in this report varied in terms of heavy/light and mandatory/voluntary use. We discuss the implications of such variations in terms of technology adoption for digital inclusion. Social factors, such as the role of parents and social communities, were found to influence women to develop and maintain interests in ICT that were reflected in their professional and personal lives. Some women were slow to adapt to ICT use as they tended to adhere to normative expectations which hindered ICT use. Women tend to have greater ICT use if it is for fulfilling familial roles and for communication.